Emerging Trends and Advanced Technologies for Computational Intelligence Extended and Selected Results from the Science and Information Conference 2015 - Chen, Liming; Kapoor, Supriya; Bhatia, Rahul (Studies in Computational Intelligence,, 2016)
This book is a collection of extended chapters from the selected papers that were published in the proceedings of Science and Information (SAI) Conference 2015. It contains twenty-one chapters in the field of Computational Intelligence, which received highly recommended feedback during SAI Conference 2015 review process. During the three-day event 260 scientists, technology developers, young researcher including PhD students, and industrial practitioners from 56 countries have engaged intensively in presentations, demonstrations, open panel sessions and informal discussions. .